BRAF inhibition curtails IFN‐gamma‐inducible PD‐L1 expression and upregulates the immunoregulatory protein galectin‐1 in melanoma cells - Patryk Górniak; Maja Wasylecka‐Juszczyńska; Iwona Ługowska; Piotr Rutkowski; Anna Polak; Maciej Szydłowski; Przemysław Juszczyński (Molecular Oncology, 2020)
Although melanoma is considered one of the most immunogenic malignancies, spontaneous T‐cell responses to melanoma antigens are ineffective due to tumor cell‐intrinsic or microenvironment‐driven immune evasion mechanisms. For example, oncogenic BRAF V600E mutation in melanoma cells fosters tumor immune escape by modulating cell immunogenicity and microenvironment composition. BRAF inhibition has been shown to increase melanoma cell immunogenicity, but these effects are transient and long‐term responses are uncommon. For these reasons, we aimed to further characterize the role of BRAF‐V600E mutation in the modulation of PD‐L1, a known immunoregulatory molecule, and galectin‐1 (Gal‐1), a potent immunoregulatory lectin involved in melanoma immune privilege. We report herein that vemurafenib downregulates IFN‐γ‐induced PD‐L1 expression by interfering with STAT1 activity and by decreasing PD‐L1 protein translation. Surprisingly, melanoma cells exposed to vemurafenib expressed higher levels of Gal‐1. In coculture experiments, A375 melanoma cells pretreated with vemurafenib induced apoptosis of interacting Jurkat T cells, whereas genetic inhibition of Gal‐1 in these cells restored the viability of cocultured T lymphocytes, indicating that Gal‐1 contributes to tumor immune escape. Importantly, Gal‐1 plasma concentration increased in patients progressing on BRAF/MEK inhibitor treatment, but remained stable in responding patients. Taken together, these results suggest a two‐faceted nature of BRAF inhibition‐associated immunomodulatory effects: an early immunostimulatory activity, mediated at least in part by decreased PD‐L1 expression, and a delayed immunosuppressive effect associated with Gal‐1 induction. Importantly, our observations suggest that Gal‐1 might be utilized as a potential biomarker and a putative therapeutic target in melanoma patients.